Pre-hospital use of ketamine for analgesia and procedural sedation. Issue 1 (22nd December 2008) - Bredmose, P P; Lockey, D J; Grier, G; Watts, B; Davies, G
Abstract : The safe delivery of adequate analgesia and appropriate sedation is a priority in prehospital care. The use of ketamine is described for analgesia and sedation in 1030 trauma patients in a physician-led prehospital trauma service. Ketamine was mainly used in awake non-trapped patients with blunt trauma for procedural sedation and analgesia. Detailed database searches did not demonstrate loss of airway, oxygen desaturation or clinically significant emergence reactions after ketamine administration. Ketamine is relatively safe when used by physicians in prehospital trauma care.